Demonstrating a separation-free process coupling ionic liquid pretreatment, saccharification, and fermentation with Rhodosporidium toruloides to produce advanced biofuels. Issue 12 (1st June 2018) - Sundstrom, Eric; Yaegashi, Junko; Yan, Jipeng; Masson, Fabrice; Papa, Gabriella; Rodriguez, Alberto; Mirsiaghi, Mona; Liang, Ling; He, Qian; Tanjore, Deepti; Pray, Todd R.; Singh, Seema; et al.
Abstract : A lignocellulose to bisabolene bioconversion process is demonstrated to be fully compatible with [Ch][Lys]. Abstract : Achieving low cost and high efficiency lignocellulose deconstruction is a critical step towards widespread adoption of lignocellulosic biofuels. Certain ionic liquid (IL)-based pretreatment processes effectively reduce recalcitrance of lignocellulose to enzymatic degradation but require either costly separations following pretreatment or novel IL compatible processes to mitigate downstream toxicity. Here we demonstrate at benchtop and pilot bioreactor scales a separation-free, intensified process for IL pretreatment, saccharification, and fermentation of sorghum biomass to produce the sesquiterpene bisabolene, a precursor to the renewable diesel and jet fuel bisabolane. The deconstruction process employs the IL cholinium lysinate ([Ch][Lys]), followed by enzymatic saccharification with the commercial enzyme cocktails Cellic CTec2 and HTec2. Glucose yields above 80% and xylose yields above 60% are observed at all scales tested. Unfiltered hydrolysate is fermented directly by Rhodosporidium toruloides – with glucose, xylose, acetate and lactate fully consumed during fermentation at all scales tested. Bisabolene titers improved with scale from 1.3 g L −1 in 30 mL shake flasks to 2.2 g L −1 in 20 L fermentation. The combined process enables conversion of saccharified IL-pretreated biomass directly to advanced biofuels with no separations or washing, minimal additions to facilitate fermentation, no loss of performance due to IL toxicity, and simplified fuel recovery via phase separation. This study is the first to demonstrate a separation-free IL based process for conversion of biomass to an advanced biofuel and is the first to demonstrate full consumption of glucose, xylose, acetate, and lactic acid in the presence of [Ch][Lys].